Association between triglyceride-glucose index and hypertension: A systematic review and meta-analysis - Lukito, Antonia A.; Kamarullah, William; Huang, Ian; Pranata, Raymond (Narra J, 2024)
The triglyceride-glucose (TyG) index is a simple and reliable indicator of insulin resistance, which is an important contributor to the development of hypertension. The aim of this meta-analysis was to determine the dose-response association between the TyG index and the incidence of hypertension. An extensive search was conducted through several databases, including PubMed, EMBASE, ScienceDirect, and Scopus until June 1, 2024. The TyG index was used as the exposure, and the incidence of hypertension was measured throughout the TyG index intervals. The effect estimates were presented as odds ratios (OR) in both the unadjusted and adjusted models. Adjusted OR were carried out from all included studies to eliminate the possibility of confounding factors being involved in the incidence of hypertension. A total of 108.936 participants (mean age: 48.2 years old, male sex: 47%, mean body mass index: 23.9 kg/m2) from 14 observational studies were included. The TyG index in the most eminent category was related to a higher risk of hypertension in both unadjusted (OR: 2.59, 95%CI: 2.03–3.31, p<0.001; I2: 97.1%, p<0.001) and adjusted model (OR: 1.74, 95%CI: 1.39–2.19, p<0.001; I2: 92.2%, p<0.001). Dose-response meta-analysis for the adjusted OR showed that the linear association analysis was not significant per 0.1 increase in the TyG index. The dose-response curve became increasingly steeper at the TyG index above 8.5. In conclusion, the TyG index was shown to be strongly linked with hypertension in a non-linear dose-response manner.